Analysis of the feminism present in the literary work "Anne of Green Gables" and its Adaptation "Anne with an E" - SILVA, Kaline da Conceição dos Santos (2024)
This article presents the interlingual and intersemiotic translation processes of the tale ‘A Procissão das Almas’ by Walcyr Monteiro from the original text in Portuguese written in prose into a comic in English. The objectives of this work were a) to create a multipurpose product that could be used to present Paraense culture internationally and in the learning of the English language by Paraense students; and b) to create interest in the world of translation studies for undergraduate students. Methodologically, we started with a bibliographical research in which the works of Jakobson (1959), Dusi (2015), Meskin (2009), Hayman and Pratt (2005), Vermeer (1978), and Holz-Mänttäri’s (1984) were referred to; then, based on the functionalist approach, we decided how to properly effectuate the translations, which were produced and then analysed. As a result, we present a short 12-page folk-horror comic adapted from the short story by Monteiro. From this work, we gathered that the field of translation studies is far-reaching, and its products can serve many a reason- as proved by ours which has multiple purposes, all which we are sure it will be able to achieve.